Long Run Inflation Indicators – Why the ECB got it Right - Fredrik N. G. Andersson (Lund University, School of Economics and Management, Department of Economics, 2008)
This paper studies the issue of whether money contains useful information about future inflation in a panel of nine developed countries. A low frequency estimate of excess money growth is compared to an estimate of the inflation trend following the discussion in Woodford (2007). The empirical analysis shows that money contains more information about future CPI-inflation than an estimate of the inflation trend, and that the output gap has some influence over the medium run movements of inflation, but the effect varies over time. The result is the same for small countries as it is for large countries. Money thus contains information about future headline inflation that the inflation trend does not.
Keywords: C19; E31; E32; E41; 330; Inflation; Money; Inflation Indicators; Wavelet Analysis